Application Of Cultural Deviance Criminology Theory to Develop Human Resources to Achieve Sustainable Development Goals (SDGS) in Karangtanjung Village, Karawang Regency - Zarisnov Arafat; Sartika Dewi; I Ketut Margayasa; Dani Durahman (Journal of Strafvordering Indonesian, 2025)
Karangtanjung Village is a village with an area of 380 Ha/m² in the Lemahabang District, Karawang Regency, with the main livelihood being agriculture.. The problem of difficulty in finding work due to the shift in the paradigm of society from agrarian to industrial areas creates inequality, thus potentially causing poverty which leads to crime problems so that it is necessary to conduct research on this phenomenon which is a concern of the Sustainable Development Goals program. Based on this, the identification of the problems raised in this study is what are the factors causing the many crimes that occur in Karawang Regency in relation to the theory of Cultural Deviance? and how are crime prevention efforts to build human resources to realize the Sustainable Development Goals program in Karangtanjung Village? This study uses a qualitative method with an empirical juridical approach. The conclusion of the researcher is that the factors causing the many crimes that occur in Karawang Regency are related to the Cultural Deviance theory, due to the increasing number of residents who do not have prospects (hopes) due to the poor social integration process which gives rise to social inequalities (potential economic sources that are still controlled by a handful of parties) and efforts that can be made to build human resources in order to realize the Sustainable Development Goals program in Karangtanjung Village are by instilling a mindset in the workforce to become entrepreneurs by utilizing the potential of the Micro, Small and Medium Enterprises (MSMEs) sector under the guidance of Village-Owned Enterprises (BUMDes) in Karangtanjung Village.